Tenderness, Juiciness, and Flavor Contribute to the Overall Consumer Beef Eating Experience - L. N. Drey; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2017)
Overall beef palatability can be attributed to three primary traits, tenderness, juiciness, and flavor, as well as the interaction among these traits (Smith and Carpenter, 1974). Multiple authors have worked to identify which of these palatability traits contributes the most to overall eating satisfaction and have historically identified tenderness as the most important palatability trait (Savell et al., 1987; Miller et al., 1995a; Savell et al., 1999; Egan et al., 2001). Overall eating quality of beef steaks may excel at one or even two of these traits, yet fail to meet consumer eating expectations due to the unsatisfactory level of another trait. Conversely, a steak may be deemed acceptable by consumers primarily due to the outstanding level of a single trait despite the lower and even unacceptable levels of one or both of the other traits. To date, no comprehensive study has evaluated this interaction among palatability traits and assessed the relative risk of an unacceptable overall eating experience associated with the failure of a single or combination of palatability traits. It was the objective of this report to combine consumer palatability data collected during the past five years as a result of a series of trials that have evaluated the palatability traits of a diverse set of treatments in order to evaluate the relative contribution of tenderness, juiciness, and flavor to overall consumer eating satisfaction.
Keywords: consumer; palatability; marbling